ANALISIS PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, TANGIBILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi pada perusahaan Barang Konsumen Primer yang terdaftar di bursa efek indonesia pada tahun 2016-2020) - Annya Helda Ayuningtyas; Wisnu Mawardi (Faculty of Economics and Business Diponegoro University, 2022)
The aim of this study was to analyze and describe the impact of Capital Structur, Firm Size, Tangibility, and Sales Growth on Firm Financial Performance with Good Corporate Governance as a Moderation Variable case in Primary Consumer Goods Sector Companies listed on Indonesian Stocks Exchange in 2016-2020. This study, sampling was taken using a purposive sampling method through the criteria determined by the researcher. The researcher managerd to get a sample of 30 companies in Primary Consumer Goods Sector Companies. The data analysis technique used is multiple linear regression analysis using IBM SPSS Statistics 26 Software. The results of this study indicate that: (1) Capital Structure has a positive and significant influence on the Firm Financial Performance; (2) Firm Size has a Positive and Significant effect on Firm Financial Performance; (3) Tangibility has a negative and significant effect on the Firm Financial Performance; (4) Sales Growth has a positive and significant impact on the Firm Financial Performance; (5) Good Corporate Governance significantly strengthents the positive impact of Capital Structure on Firm Financial Performanve; (6) Good Corporate Governance significanly not strengthens the positive impact of Firm Size on Firm Financial Performance